A Systematic Literature Review on Earthquake Detector - Mat Nor, Ahmad Hakimi; Sanik, Mohd Erwan; Salim, Salman; Kaamin, Masiri; Osman, Mohamad Hairi; Fuzairi, Naeeman; Alia, Amani; Nur Qurratu’ Ain (Multidisciplinary Applied Research and Innovation, 2021)
Around the world, earthquakes continue to be a significant cause for death, injury and disruption. Recently, Malaysia startled by Sabah earthquake that struck Ranau, Sabah on 5 June 2015 with moment magnitude reported 6.0   by the United States Geological Survey while the Malaysia Meteorological department has reported the magnitude to be 5.9   at a depth approximately 10 km with it is epicenter approximately 15 km North of Ranau and which lasted for 30 seconds. There are four objectives in this review paper which are review the vary keywords used in research, studies the different types of earthquakes detector that are appropriate, review the effectiveness of earthquake detectors and the effects of installation on environment and lastly examination the output produced by the earthquake detectors through the created/ existing detectors. There are four phases involved in this part which are identification, screening, eligibility, included. Each of phases shows the flow to determine references from resources search. After identify, based on all this steps, there are only 35 articles that included in qualitative synthesis. All findings studies were discussing and analyzed based on keyword used, types of detectors, output that produce from earthquake detectors and its effects on humans, technologies and environments. From studies that has been run, there are several ideas will be recommend in this part for future studies and for the benefit of researcher. Firstly, the devices will produce the location of the nearest earthquake protection center. Next, earthquake detectors can detect heat from humans or animal within a range of distances.